Роль анімації в UX/UI дизайні веб-сайтів - Римаренко, О. Г. (ХНУРЕ, 2024)
This work is dedicated to the role of animation in UX/UI design of web sites. Various aspects of animation usage are considered, including accent and hover animations, and their impact on user experience. The role of animation in enhancing navigation and creating attractive web interfaces is discussed. The use of software, particularly After Effects, for creating animation effects is also examined. Overall, this work highlights that animation plays a crucial role in web design, ensuring effective user interaction with the website. It's clear that in web design, animation becomes a powerful tool, helping to create not only functional but also aesthetically appealing interfaces for users.
Keywords: дизайн веб-сайтів; анімація